Low-intensity aerobic cycle ergometer effects on lung function of myasthenia gravis patients: A randomized controlled trial - Amalina, Nabila; Poerwandari, Dewi; Handajani, Noor I.; Sudibyo, Devi A.; Melaniani, Soenarnatalina (Narra Sains Indonesia, 2024)
Patients with generalized myasthenia gravis (MG) often show restrictive spirometry results. Although regular exercise and physical fitness are linked to better respiratory function, there is limited research assessing the effects of aerobic exercise on lung function in MG patients. The aim of this study was to analyze the effect of low-intensity aerobic exercise using a cycle ergometer on lung function parameters in MG patients. A randomized controlled trial with pre- and post-test was conducted at the Medical Rehabilitation Outpatient Clinic of Dr. Soetomo General Academic Hospital in Surabaya, Indonesia, in 2023. MG patients classified as I−IIb based on the Myasthenia Gravis Foundation of America (MGFA) classification were recruited and randomly divided into treatment and control groups. The treatment group was given low-intensity aerobic exercise using a cycle ergometer, education on lifestyle changes, and breathing exercises (deep and pursed lip breathing). Lung function parameters, including forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), and forced expiratory volume ratio (FEVR), were then measured. Measurements were conducted before and after eight weeks of low-intensity aerobic cycle ergometer exercise and compared with those of a control group. A total of 17 MG patients were included in this study. The results showed a significant increase in FVC in the treatment group (p=0.003), whereas no significant change in the control group (p=0.068). A significant increase in FEV1 was observed both in the treatment (p=0.029) and the control group (p=0.016). There was no improvement in FEVR in either group. After the intervention, significant differences were observed in FVC (p=0.009) and FEV1 (p=0.029) between the treatment and control groups. There was no significant difference in FEVR values after the intervention between both groups (p=0.491). In conclusion, eight weeks of low-intensity aerobic cycle ergometer exercise led to significant improvements in FVC and FEV1 among MG patients.